ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL BANGUN RUANG SISI DATAR - Ratih Pratiwi; Ika Wahyu Anita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The study was conducted to analyze students errors when solving problems with flat side space. The method used in this research is descriptive qualitative. The research subjects were 25 grade IX students from SMP Negeri 10 Cimahi for the 2020-2021 academic year. In the data collection stage, the researcher gave a description of the questions to the students, then corrected the results of the students answers, then analyzed some of the students answers as a sample. The percentage results show that the largest percentage of student error answers number 2 is 68% while the lowest percentage number 4 is 8%. The results of the study of student errors that often occur are confusion when solving problems because they do not understand the questions, are less careful when reading questions and are less careful when calculating and forgetting formulas. The contributing factor: students do not master the concept, only refers to memorizing formulas without knowing the origin of the BRSD formula which causes students to override basic concepts and lack mastery of prerequisite materials.